THE INFLUENCE OF SOCIAL MEDIA CONTENT (TIKTOK) ON THE MENTAL HEALTH OF JUNIOR HIGH SCHOOL STUDENTS - Millah, Jauharotul; Indahwati, Septiana; Hasanah, Havidhotul (International Conference on Humanity Education and Society (ICHES), 2024)
Tiktok is a social media platform that is currently popular and offers a variety of content, from entertainment to education. However, Tiktok has a significant impact on the mental health of students, especially at the junior high school level who are at a stage of development that is vulnerable to being influenced by social media that is currently developing. The aim of this research is to see how far the impact is, and how to prevent risks to handle this for students at one of SMPN 3 Songgon in Banyuwangi. This research uses quantitative methods with linear regression analysis techniques at a significance level of 5% or 0.05. The sample used was 15% of the population of 200 students, namely 40 respondents, with sampling using the Stratified Random Sampling technique. Data analysis used the Simple Linear Regression test. The research results can be concluded that the influence of social media has a negative and significant effect on mental health, excessive social media causes anxiety, stress, depression and loneliness in teenagers. This research resulted in 74.9% of teenagers being identified as having mental health or being in the moderate category.